P3.114 Are Male Sex Workers in Tel-Aviv, Israel at Higher Risk to Getting STI and HIV Than Men Who Have Sex with Men. (13th July 2013) - Mor, Z; Dan, M
Abstract : Background: The number of men who have sex with men (MSM) newly diagnosed with HIV in Israel has quadrupled since 2000. Male sex workers (MSW) are often associated with risk behaviours and STI/HIV infections; thus, they may play a role as core group transmitters. This study aimed to explore knowledge, attitudes and sexual-practises of MSW in Tel-Aviv in comparison with MSM, classified by their risk-behaviours, and to outline attributes related to STI/HIV-prevalence. Methods: MSW were recruited for this cross-sectional study from designated street venues and gay-dating internet-site. MSM were recruited from gay-related venues and divided into high-risk MSM (HRMSM) if they performed unprotected anal intercourse in the last six-months with a HIV-discordant/unknown partner, and to low-risk MSM (LRMSM). Each participant completed a questionnaire and was tested for STI/HIV. Results: Of 87 MSW and 635 MSM approached, 53 (60.9%) and 235 (37.0%) participated, respectively. Street-MSW (N = 32) had more female sex partners and were more drug-dependant than internet-MSW (N = 21). No differences were found in their knowledge regarding STI/HIV transmission, practises and STI/HIV burden. Compared to HRMSM, MSW had different demographic attributes and demonstrated more realistic perception regarding the risk to getting STI/HIV, while no differences were found in their knowledge and sexual practises. STI and HIV burden among MSW, HRMSM (N = 119) and LRMSM (N = 116) were 28.3%, 23.5%, 10.3%, and 5.6%, 9.2%, 0%, p = 0.009 and 0.001, respectively. Multivariate models evaluating attributes associated with HIV/STI-diagnosis did not find sex-work to be significant if the variable used was MSW vs . HRMSM, regardless of the adjustments performed. However, when MSW vs . LRMSM was used in the model, sex-work was associated with STI/HIV-diagnosis. Conclusions: Street-MSW and internet-MSW shared comparable sexual practises and no difference was found in their STI/HIV burden. Likewise, MSW and HRMSM had comparable sexual practises and no difference in STI/HIV prevalence.